Che ne pensi, elettore? Un sondaggio all’uscita dai seggi nelle elezioni comunali del 2012 in un borgo toscano - Mattia Forni (QOE-IJES, 2014)
This article provides a deep description about local politics in Rignano sull’Arno, a small village near Florence, focusing on the features of “red” territorial political subculture that have ceased to exist, as well as those that still remain a part of voters’ behaviour. To begin with, I will draw attention to the political and electoral history of the village since 1946; going on to describe the main traits of local electors, with reference to a survey that accounted for 1220 voters, carried out during the 2012 administrative elections. I will concentrate on social and demographic characteristics, searching for a link between these qualities and the electoral results. From here I will examine the voting patterns of the local population and the motives behind such voting behaviour. I will consider the main role played by candidate’s personal characteristics in infl uencing the voters, to the detriment of party identifi cation, political values and ideology, which are becoming less and less relevant. Further topics I will illustrate in this paper are the types of sources that people gathered their information from during the election campaign and the time at which they decided how to vote. Finally, electoral instability and the changes in voter’s behaviour between the last two local elections will be analysed.